1985
DOI: 10.1088/0264-9381/2/2/001
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of the S 5 compactification of the chiral N=2, D=10 supergravity and the unitary supermultiplets of U(2,2/4)

Abstract: Abstract. We calculate the spectrum of the S5 compactification of the chiral N = 2, D = 10 supergravity theory. The modes on S5 fall into unitary irreducible representations of the D = 5, N = 8 anti-de Sitter supergroup U(2,2/4). These unitary supermultiplets involve fields of spin s 2 with quantised 'mass' eigenvalues. The massless multiplet contains fifteen vector fields, six self-dual and six anti-self-dual anti-symmetric tensor fields. The fields of the massless multiplet are expected to be those of a gaug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
622
0
4

Year Published

1998
1998
2005
2005

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 334 publications
(640 citation statements)
references
References 17 publications
14
622
0
4
Order By: Relevance
“…In this section we will show how to represent a generic operator of N = 4 SYM in terms of excitations of (different) oscillators, see also [34]. We will then describe the action of the Hamiltonian on these states explicitly.…”
Section: The Oscillator Picturementioning
confidence: 99%
“…In this section we will show how to represent a generic operator of N = 4 SYM in terms of excitations of (different) oscillators, see also [34]. We will then describe the action of the Hamiltonian on these states explicitly.…”
Section: The Oscillator Picturementioning
confidence: 99%
“…The short representations of P SU (2, 2|4) were constructed by the oscillator method in [26]. The full short representation is labeled by an integer p > 0 and consists of a number of particular representations of the bosonic SU (2, 2) × SU (4) R subgroup.…”
Section: Representations Of the Superconformal Group P Su (2 2|4) Anmentioning
confidence: 99%
“…The compactification of the supergravity on S 5 creates a tower of massive particles on AdS 5 , and their spectrum is classified in [8,9]. Curiously they found that all the eigenvalues of H are integers, including excitations on AdS 5 .…”
mentioning
confidence: 99%